FeMnO3: Synthesis, Morphology, Dielectric Properties, and Electrochemical Behavior Toward HER by LSV - Mataev, Mukhametkali; Sarsenbaeva, Zamira; Nurbekova, Marzhan; Krishnamoorthy, Ramachandran; Keskin, Bahadir; Abdraimova, Moldir; Tursyn, Zhanar; Seitbekova, Karima; Durmenbayeva, Zhadyra (MDPI, 2026)
This paper presents a comprehensive investigation into the synthesis, morphological characteristics, electrical conductivity, dielectric behavior, and electrocatalytic activity of perovskite-structured iron manganite (FeMnO3), with a specific focus on its performance in the hydrogen evolution reaction (HER). FeMnO3(FMO) nanoparticles (NPs) were synthesized using a sol-gel-type Pechini method and characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and field-emission scanning electron microscopy combined with energy-dispersive X-ray spectroscopy (FESEM-EDS). XRD analysis confirmed the formation of a crystalline structure with cubic symmetry assigned to the Ia-3 space group, with an average crystallite size of 52.47 nm. FESEM images revealed a relatively uniform morphology with an average particle diameter of 55.84 nm. The redox and oxidation states of Fe and Mn can be studied by temperature-programmed oxidation (TPO-O-2) in order to understand oxygen uptake and metal oxidation processes occurring within the FMO lattice. The dielectric constant, dielectric loss, electric modulus and electrical conductivity were calculated as a function of frequency and temperature using a Novocontrol Alpha-A broadband dielectric spectrometer (Novocontrol system) coupled with the LCR-800 precision meter. The dielectric data reveal that the FMO has semiconducting behavior with dominant charge- or ionic-relaxation processes. The electrocatalytic activity toward the HER was evaluated using linear sweep voltammetry (LSV), with the working electrode modified by an FMO catalyst ink. The material exhibited significant catalytic activity within the HER potential range, and an increase in the number of cycles led to stabilized current and enhanced hydrogen evolution. These results highlight the stability of FeMnO3 for hydrogen generation.
Keywords: FeMnO3; perovskite-like; synthesis; dielectric properties; linear sweep voltammetry; IRON; PEROVSKITE; OXIDATION; CATALYST; Chemistry; Science & Technology - Other Topics; Materials Science; Physics